The educational impact of broadband subsidies for schools under E-rate. Issue 5 (4th July 2019) - Hazlett, Thomas W.; Schwall, Ben; Wallsten, Scott
ABSTRACT: In 1998, the U.S. began spending about $2 billion annually to help fund computer access in elementary and secondary schools. In 2013, the Federal Communications Commission, citing the experience of a school district in North Carolina, increased these annual 'E-Rate' subsidies to $4 billion. Do such expenditures actually improve academic achievement? We estimate a model wherein SAT scores, a proxy for student performance, are a function of explanatory factors including federal broadband funding. Examining data from all North Carolina public high schools, 2000–2013, we find no gain in student test results associated with Internet subsidy levels.